Thomas Wallerström, Kunglig makt och samiska bosättningsmönster. Studier kring Väinö Tanners vinterbyteori: [English summary: Royal power and Sámi settlement patterns. Studies concerning Väinö Tanner’s winter camp theory. With contributions from Ulf Segerström and Eva-Maria Nordström] - Aronsson, Kjell-Åke (Journal of Northern Studies, 2021)
Review of: Thomas Wallerström, Kunglig makt och samiska bosättningsmönster. Studier kring Väinö Tanners vinterbyteori (English summary: Royal power and Sámi settlement patterns. Studies concerning Väinö Tanner’s winter camp theory. With contributions from Ulf Segerström and Eva-Maria Nordström), Oslo: Novus forlag 2017, ISBN 9788270999071, 322 pp.